Comunicação interpessoal: ensino de algumas habilidades desejadas - Bachion, Maria Márcia (1994)
Aiming at helping the utilization ofcommunicative skills by nursing undergraduate students when interacting with patients carriers of chronical-degenerative diseases, we carried through a quasi-experiment in which we organized a WORKSHOP (10 meetings of2 hours each) including, among other activities, three programmed interviews for the purpose of determining initially the base line ofthe subjects' interaction and the training effect in the application of communicative skills. 6 undergraduate students ofthe third year developed all the stages. The model ofFORREST (1983) was adopted as a theoretical reference, ■which proposes 9facilitator categories and 9 blocker categories. In the conclusion ofthe Workshop, the individuais had modified their pattern of oral emission, related to the facilitator and blocker categories. These alterations were not statiscally significant, excepting the subcategory F1 (question of opening), -when applied the Wilcoxon test. The subjects 1, 2, 3, 4, 5 and 6 had, in the third intervíew, the best performance interacting with vatients. The subject 2 had the best performance in the second interview. We believe that inly applied courses, with practical activities, feedback and repetition, are able to change Sehaviours ofundergraduate students related to communication. Informative courses reach he cognitive levei of apprenticeship. However, it is necessary to reach it in the affective ■>oint of view. The applied Model was appropriate to teaching activities as well as to the inalysis ofinteractions.